Direct and Efficient Plant Regeneration from Different Explants Sources of Potato Cultivars as Influenced by Plant Growth Regulators - Dhital, Shambhu P.; Lim, Hak T.; Manandhar, Hira K. (Nepal Journal of Science and Technology, 2012)
Response of widely grown potato cv. Superior and newly developed cvs. Gui valley and Bora valley to plant growth regulators (PGRs) for direct plant regeneration from internode, leaf blade and petiole explants were investigated. The explants were cultured on a MS solid medium supplemented with different concentrations and combinations of 6-benzylaminopurine (BAP), 1-naphthaleneacetic acid (NAA), zeatin, indole-3-acetic acid (IAA) and gibberellic acid (GA3). Potato cv. Superior, regenerated direct shoot without callus and root formation on MS solid medium supplemented with BAP or zeatin, proliferous roots were produced on NAA or IAA supplemented medium and only some calli were produced on GA3 supplemented medium. The regeneration response varied with different concentrations of PGRs, singly and also in combinations. In the case of combined application of PGRs, the highest shoot regeneration (75.3%) and number of shoot per explant (11.5) and number of roots per explant (7.0) were obtained from the MS solid medium supplemented with zeatin (2 mg l-1), NAA (0.1 mg l-1) and GA3 0.1 mg l-1). Among the three types of explants evaluated, internodes produced the highest number of shoots and roots for both potato cvs. Gui valley and Bora valley, and petiole produced the least number of shoots and roots. The regenerated shoots were rooted in PGRs-free MS solid medium and successfully established under glasshouse condition. Leaf, flower, and tuber morphology were identical to in vitro control and mother plants in the same conditions. This optimized regeneration system can be used for rapid shoot proliferation and also for gene transformation. DOI: http://dx.doi.org/10.3126/njst.v12i0.6471 Nepal Journal of Science and Technology 12 (2011) 1-6